Tecnologia no tratamento de águas residuárias - Macagnan, Daiany Crystina (2011)
The wastewater is generated daily in all the activities that need water in their process, whether health activities for residential and commercial or manufacturing processes of enterprises. This study evaluated the efficiency of the microalgae Scenedesmus in nitrogen and phosphorus removing from brewery wastewater. Two experiments were conducted at different times in three replicates of each one packaged in boxes of fiberglass 100L. Each treatment was made for a completely randomized design with three different concentrations of wastewater. The collect of wastewater was made at different times. The medium was constituted of 80L of wastewater and five liters of inoculated culture of microalgae Scenedesmus sp. We evaluated the growth curve, phosphate and nitrogen compounds removal, the correlation between the removal of compounds with algal growth, yield and protein biomass. Higher algal density was observed in the treatment 6 (T6) medium with 776 x 104 cells / mL and all treatments had high coefficients of determination (R2) ranging from 0.87 to 0.99 in T4 at T6. In the experiment 1 the removal of the compounds in the treatments occurred in 17 days. In experiment 2 the nitrate removed in 17 days in all treatments and orthophosphate and phosphorus removal occurred between nine to 24 days. Generally, the correlations ranged from moderate to strong, with the exception of total phosphorus in T4 which showed a weak correlation (-0.08).The biomass and crude protein in experiment 1 ranged from 0.15 to 0.19 g / L and 19 to 27% respectively, while those in experiment 2 ranged from 0.12 to 0.19 g / L and 34 to 46% protein. It is concluded that biological treatment from microalgae is able to reduce the nitrate, phosphorus and orthophosphate present in the brewery wastewater, producing biomass with high protein values.